Measurement tools in the assessment of body image in the dancing context: a systematic review - Natalia Fraga-Pena; Marta Bobo-Arce (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Body image is the mental representation an individual makes about their body. In the dancing context, aesthetic is a significant factor, as body image is. Objective: The aim of this systematic review was to identify which were the most used measuring tools for assessing body image in the dancing context, analyse them and conclude which ones were most suitable in this field.  Methodology: Following PRISMA guidelines, articles were gathered from Web of Science, Scopus and PubMed databases up to March 7th, 2023. Primary studies of any design and language were eligible if they assessed body image in adult dancers.  Results: Eighty-eight studies were included. In qualitative studies, in-depth interviews were the most common tool. In quantitative studies, more than thirty scales were identified, but only seventeen were found to be used at least twice, including silhouette scales and questionnaires. The Stunkard Scale was the most frequently used. Discussion: Only two scales were found to be specifically designed for dancers and neither of them was commonly used in literature.  Conclusions: Stunkard Scale, in-depth interviews, Body Appreciation Scale and Body Shape Questionnaire are the most used instruments for assessing body image in dancers. Qualitative methods offer relevant information for the comprehension and exploration of body image. Quantitative methods are also useful, although silhouette scales offer a binary view of bodies and genders and should be reevaluated.